The Problem of Secularism and Formalism Models and the Relationship between the State and Religion - Abdul Hakim; Misdin Arifin; Imamuddin (Jurnal Sahabat ISNU SU, 2025)
The discourse between Islam and the state remains a hot topic in Islamic thought. Among these, there are three models of the relationship between religion and the state: formalism, which promotes the unity of Islam and the state, and secularism, which advocates the absolute separation of Islam and the state. Both have logical foundations and refer to original sources. Debate between the two is inevitable, therefore, discussions on this topic remain heated. The authors highlight Abu A'la al-Maududi and Sheikh Ali Abd. Rajik. Both are Islamic thinkers who have written extensively on the model of Islam and the state. They have also engaged in serious debates regarding these issues.